SPE Latin American and Caribbean Petroleum Engineering Conference 2015
DOI: 10.2118/177270-ms
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Adaptive-Predictive Control and Optimization of SAGD under Uncertainty

Abstract: When it comes to SAGD optimization, two of the biggest challenges are controlling subcool to achieve conformance (a uniform growth of the steam chamber along the complete length of the well pair), and maximizing an economic performance measure, such as net present value (NPV); both desirable outcomes are not necessarily associated with the same values of the operational parameters (e.g., injection rates). Overcoming these challenges is necessary for achieving optimum SAGD performance, but this may be difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Gharbi [26] presented an EOR expert approach to optimize reservoir management and CO 2 floods in carbonate reservoirs. Several studies have focused on optimizing NPV of EOR projects under uncertainty [27][28][29]. These studies only focused on optimizing oil recovery rather than CO 2 storage.…”
Section: Introductionmentioning
confidence: 99%
“…Gharbi [26] presented an EOR expert approach to optimize reservoir management and CO 2 floods in carbonate reservoirs. Several studies have focused on optimizing NPV of EOR projects under uncertainty [27][28][29]. These studies only focused on optimizing oil recovery rather than CO 2 storage.…”
Section: Introductionmentioning
confidence: 99%
“…In another work, Guevara et al used nonlinear neural network‐based ARMAX models in MPC for subcool and compared its performance with a decentralized PID control strategy. The authors concluded that while their approach offered a slower response, it outperformed the PID control overall in terms of steady state behaviour and control energy spending.…”
Section: Introductionmentioning
confidence: 99%